Autocrine release of angiopoietin-2 mediates cerebrovascular disintegration in Moyamoya disease. Issue 4 (April 2017) - Blecharz, Kinga G; Frey, Dietmar; Schenkel, Tobias; Prinz, Vincent; Bedini, Gloria; Krug, Susanne M; Czabanka, Marcus; Wagner, Josephin; Fromm, Michael; Bersano, Anna; Vajkoczy, Peter
Moyamoya disease is a rare steno-occlusive cerebrovascular disorder often resulting in hemorrhagic and ischemic strokes. Although sharing the same ischemic stimulus with atherosclerotic cerebrovascular disease, Moyamoya disease is characterized by a highly instable cerebrovascular system which is prone to rupture due to pathological neovascularization. To understand the molecular mechanisms underlying this instability, angiopoietin-2 gene expression was analyzed in middle cerebral artery lesions obtained from Moyamoya disease and atherosclerotic cerebrovascular disease patients. Angiopoietin-2 was significantly up-regulated in Moyamoya vessels, while serum concentrations of soluble angiopoietins were not changed. For further evaluations, cerebral endothelial cells incubated with serum from these patients in vitro were applied. In contrast to atherosclerotic cerebrovascular disease serum, Moyamoya disease serum induced an angiopoietin-2 overexpression and secretion, accompanied by loss of endothelial integrity. These effects were absent or inverse in endothelial cells of non-brain origin suggesting brain endothelium specificity. The destabilizing effects on brain endothelial cells to Moyamoya disease serum were partially suppressed by the inhibition of angiopoietin-2. Our findings define brain endothelial cells as the potential source of vessel-destabilizing factors inducing the high plasticity state and disintegration in Moyamoya disease in an autocrine manner. We also provide new insights into Moyamoya disease pathophysiology that may be helpful for preventive treatment strategies in future.